Designing eHealth Tutorials with and for Older Adults. Issue 1 (13th October 2021) - Davis, Nathan; Shiroma, Kristina; Xie, Bo; Yeh, Tom; Han, Xu; De Main, Atami
Abstract: Older adults may be excluded from using digital health technologies due to limited eHealth literacy. Research is much needed to decrease disparities in eHealth literacy and increase the inclusiveness of such technologies. Integrating the preferences and expertise of older adults is key to age‐appropriate design of eHealth tutorials. This study explores how participatory design (PD) techniques can be adapted to include older adults in the design of an eHealth tutorial. We worked with 9 older adults (aged 64 and 82) as co‐designers and conducted PD sessions over 11 weeks in a senior center's computer lab. Using thematic analysis, we identified 7 themes around the design of eHealth tutorials for older adults. We also identified successes and challenges in PD with older adults, along with benefits of partnering with senior centers. Our findings have implications for both the design of eHealth tutorials for older adults and for PD with older adults.